STUDI LITERATUR: RELEVANSI NILAI INFORMASI AKUNTANSI TERHADAP HARGA SAHAM - Cindy Vinella; Jason Wibisono; Maya Rianti; Maria Ellita Ovina; Carmel Meiden (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
The purpose of this study is to provide an overview of the relevance of the value of accounting information to stock prices. This research was conducted using a Systematic Literature Review (SLR) methodological approach to identify, study, evaluate, and interpret all available research with relevant research questions. To search for journals related to the research topic, researchers use search keywords: “value relevance”, “accounting information”, and “stock price.” This study discusses important aspects of research such as research topics, research methods, and theories used in 40 published literature reviews that were collected during the research period from 2015 – 2022. To enrich the results, this study discusses several other aspects, such as the year of research, methodology, and country of research. The results showed that during the period 2015 – 2022, the most frequently used research topics were related to the influence of accounting information and stock prices. The most frequently used research method is incremental association studies. While the theory most often used is signaling theory. The results of this study provide information for future researchers who will examine value relevance to be used as a reference in developing their research.